Perbandingan Efisiensi Dan Fleksibilitas Pengembangan Antara Pendekatan Konvensional dan Pendekatan Low-Code Pada Sistem Informasi Kepegawaian - Clara Meyhazlinda Putri; Muhammad Rachmadi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
PT Pratista Shaqu Unggul is a company operating in the field of General Contractor, Supplier and Maintenance. PT Pratista Shaqu Unggul has 30 permanent employees and approximately 5-10 non-permanent employees. PT Pratista Shaqu Unggul has difficulties in storing and managing employee data which has not been properly integrated. Based on this, the personnel information system at PT Pratista Shaqu Unggul was created with the aim of making it easier for the company to manage employee data. The development of this system uses the RUP (Rational Unified Process) method and is created using two approaches, namely the conventional approach and the low-code approach. The conventional approach uses the Laravel framework and the low-code approach uses FlutterFlow. The research results obtained are a web-based personnel information system that meets user needs for managing recruitment, attendance, leave and layoff data.